Studies оf Ice-forming Properties of Zinc Oxide Nanotube Clusters - B. М. Khuchunaev; A. H. Budaev; Kh. A. Tumgoeva (Наука. Инновации. Технологии)
Introduction. In recent years, the volume of funds used in the practice of weather modification has been growing in the world. Silver, the main component of weather modification funds, is a rather expensive metal. Therefore, the issue of reducing the silver content in the formulations of pyrotechnic compositions or the use of other effective ice-forming agents is relevant. Zinc oxide, like silver iodide, has ice-forming properties. When zinc is sublimated in water vapor, clusters of nanotubes of various sizes are formed. In this regard, experimental studies of the mechanism of ice formation on clusters of zinc oxide nanotubes seem to be an urgent task. The results of these studies are presented in this article.Materials and research methods. During thermal sublimation of reagents nanoscale particles are formed. These particles combine into clusters. The shape and size of these clusters, as well as their ice-forming properties, depend on the thermodynamic state of the medium in which they are formed. Tests of the ice-forming efficiency of such reagents should be carried out in conditions in clouds. This article presents the results of laboratory modeling of the formation of ice crystals during the interaction of zinc oxide clusters consisting of nanotubes, and the results of their comparison with the pyrotechnic composition AD–1 used in practice of weather modification, which is used in anti-hail products of the type «Alazan–6» and «Alazan–9» [1].Research results and their discussion. The article presents the equipment and methods of performing experiments to study the ice-forming properties of clusters of zinc oxide nanotubes obtained in a cloud chamber during zinc sublimation in the presence of water vapor. The experiments were carried out on laboratory installations in the temperature range from –3 to –14 °C. The effectiveness of a reagent based on clusters of zinc oxide nanotubes has been investigated and compared with the effectiveness of the pyrotechnic composition of AD–1. The research results are presented in Tables 1–6 and Figures 2–7.Conclusions. In the course of laboratory experiments, a method for studying the ice-forming properties of clusters of zinc oxide nanotubes has been developed. When the pyrotechnic composition of AD–1 is sublimated, particles with a diameter from 20 nm to 400 nm with a modal value of 70 nm are formed. Zinc oxide clusters have a porous, loose structure, low density and larger sizes, almost two orders of magnitude larger than the sizes of silver iodide particles. Large ice crystals are formed on them. The total area of crystals formed on clusters of zinc oxide nanotubes is an order of magnitude larger than the total area of crystals formed on particles of the pyrotechnic composition AD–1. The reagent consisting of zinc oxide clusters is comparable in ice-forming characteristics to the pyrotechnic composition of AD–1 and can be recommended for practical use.